Hospitality language as a professional skill - Blue, George M.; Harun, Minah (Elsevier Science Ltd., 2003)
International travel is a rapidly growing activity entailing cross-cultural communication between hosts and guests from different linguistic backgrounds. There is therefore a growing worldwide need for front-line staff(as hosts) in the hospitality industry who are able to communicate effectively with guests.This paper argues that particular patterns of language are associated with host-guest interaction. This language, corresponding to the different stages of the arrival–departure hospitality cycle, may be termed ‘hospitality language’. The first two parts of the paper investigate hospitality practices and define the notion of hospitality language, outlining its evolution in the context of the United Kingdom. This is followed by an illustration of its use in a case study of four hotels in Southampton. The fourth part discusses some pedagogical implications, with an emphasis on the need to expose learners to actual hotel reception practices. Interviews with hotel staff reveal that some hospitality skills could be developed through in-service training. It is argued that such training could be viewed as an ESP/EOP requirement of the hospitality profession.The concluding section recommends that communication skills be given more serious attention by human resources managers, researchers and educators in the field of hospitality management.